Pyrolytic studies of carbonaceous matter in Antarctic carbonaceous chondrites - Murae, Tatsushi; Masuda, Akimasa; Takahashi, Takeyoshi (1987)
P(論文) Pyrolysis products of the major carbonaceous matter in six Antarctic carbonaceous chondrites, Y-74662 (C2), Y-791198 (C2), Y-793321 (C2), B-7904 (C2), Y-791717 (C3), and ALH-77307 (C3), have been examined by GC-FID and GC-MS. There is apparently a similarity in the structure of all samples. Many sulfur-containing compounds have been detected as major products in pyrolysis of the residues which were obtained by partial mineral dissolution of Y-791717 and ALH-77307 with concentrated hydrochloric acid. departmental bulletin paper